2018
DOI: 10.1590/0100-29452018491
|View full text |Cite
|
Sign up to set email alerts
|

Heat unit accumulation and inflorescence and fruit development in ‘Ubá’ mango trees grown in Visconde do Rio Branco-MG

Abstract: There are little information in the scientific literature on flowering and fruiting of 'Ubá' mango trees. These information enables to know the proportion of hermaphrodite flowers in inflorescence, fruit set percentage and developmental stages of the fruit. In this study evaluations on inflorescence and fruit development of the 'Ubá' mango tree (Mangifera indica L.) were carried out, as well as the determination of the required number of heat units for full fruit development. Thirty branches whose terminal bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The maximum, minimum and mean temperatures during the study period were recorded (Figure 1) and DD under different phenological stages was worked out. Considering the climatic preference of tamarind (tropical) a base temperature of 10 C was considered to work out thermal time requirement (DD) at different phenological stages (Lemos et al, 2018;Souza et al, 2015):…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum, minimum and mean temperatures during the study period were recorded (Figure 1) and DD under different phenological stages was worked out. Considering the climatic preference of tamarind (tropical) a base temperature of 10 C was considered to work out thermal time requirement (DD) at different phenological stages (Lemos et al, 2018;Souza et al, 2015):…”
Section: Methodsmentioning
confidence: 99%
“…The maximum, minimum and mean temperatures during the study period were recorded (Figure 1) and DD under different phenological stages was worked out. Considering the climatic preference of tamarind (tropical) a base temperature of 10°C was considered to work out thermal time requirement ( DD ) at different phenological stages (Lemos et al, 2018; Souza et al, 2015): DD=t=1nTmax+Tmin/2Tb where DD is the degree days; T max is the daily maximum air temperature (°C); T min is the daily minimum air temperature (°C); T b is the base temperature (°C) and n is the number of days of specific growth stage. Weather information during the study period was obtained from the Meteorological Centre located 6 km away from the site.…”
Section: Methodsmentioning
confidence: 99%
“…Cultivar Tb ( [3] Calypso 10 n/a Christmas tree 1640 adjacent Australia [2] Honey Gold 12 n/a asparagus 1800 on farm Australia [4] Honey Gold 12 n/a Christmas tree 1500 adjacent Australia [2] R2E2 12 n/a asparagus 1800 on farm Brazil [5] Tommy Atkins 13 32 Christmas tree 1428 adjacent Brazil [6] Tommy Atkins 13 32 fruit set 1158 adjacent Brazil [7] Alfa 10 n/a Christmas tree 2117 1 km from farm Brazil [8] Roxa 10.6 n/a pea size fruit 1710 n/a Brazil [9] Uba 10 n/a bud swelling 2399 n/a Mexico [10] Tommy Atkins 10 n/a Christmas tree 1600 inside canopy Mexico [10] Keitt 10 n/a Christmas tree 2100 inside canopy Mexico [10] Kent 10 n/a Christmas tree 1800 inside canopy Mexico [10] Ataulfo 10 n/a Christmas tree 1600 inside canopy India [11] Alphonso 10 n/a fruit set 1867 n/a India [11] Alphonso 17.9 n/a fruit set 919 n/a India [12] Kesar 17.9 n/a fruit set 1020 n/a References: Diczbalis et al [1], Moore [2]; Hofman et al [3]; Winston et al [4], Castro et al [5], Rodrigues et al [6], Barros et al [7], Callejas et al [8], Lemos et al [9], Osuna-Garcia [10], Zagade et al [11], Halepotara et al [12].…”
Section: Locationmentioning
confidence: 99%
“…The US National Mango Board [16] has The stages of flower development vary in duration (Figure 1). Lemos et al [9] reported 182 to 276 GDD (equivalent to 14-21 days) from bud swelling to flower initiation (a), then 623 GDD from bud swelling to flower opening (equivalent to 49 days) (c) using Equation (1). with a Tb of 10 for mango cv.…”
Section: Estimating Harvest Maturitymentioning
confidence: 99%
“…A properly timed harvest requires a determination of the physiological maturity stage of the fruit, which be identified by physical parameters, such as longitudinal length, equatorial diameter, mass, shape, color and firmness, and/or with chemicals using the soluble solids content, titratable acidity, and pH, among others. However, one of the criteria used in determining the harvest point is number of days of anthesis until full development of the fruit (Warrington et al, 1999;Lemos et al, 2018).…”
Section: Physiological Maturity Of Pitaya Fruitsmentioning
confidence: 99%